Strategies used by Indonesian high school English teachers to improve students' reading comprehension: A qualitative study - Fitria, Risa; Widyantoro, Agus; Sukarno, Sukarno (Universitas Islam Negeri Banda Aceh, 2024)
Reading comprehension is essential in ESL/EFL teaching, yet many students in Indonesia face difficulties in comprehending English passages. This study aims to investigate the strategies used by English language teachers to address these challenges. The research problem focuses on identifying effective strategies to improve students' reading comprehension skills. A qualitative research method was used, involving semi-structured interviews with four high school English teachers in Indonesia who were purposively selected. Data were collected in January 2024 through interviews conducted at different times and locations. The data were analyzed thematically to identify recurring challenges and effective strategies. The findings revealed that teachers faced significant barriers, such as students' limited vocabulary and difficulties with long texts. To address these issues, teachers used strategies such as selecting passages based on students' interests, using skimming and scanning techniques to quickly identify key ideas and specific information, and using mind mapping to help students organize and understand complex information. In conclusion, the study highlighted the importance of adaptive teaching methods in overcoming reading comprehension challenges. The suggested strategies - interest-based texts, skimming, scanning and mind mapping - were found to be effective in improving students' reading skills. Further research is recommended to investigate the long-term effects of these strategies and to develop additional methods for improving reading comprehension.